Self-Determination v Remedial Secession: The Status of Republic of Artsakh (Nagorno-Karabakh) under International Law - Wulan Christianti, Diajeng (International Law Department, Faculty of Law Universitas Padjadjaran, 2024)
Nagorno-Karabakh is a region situated between Azerbaijan and Armenia, which has been the subject of a territorial dispute between the two neighbouring countries. The region declared independence as Republic of Artsakh and separated from Azerbaijan. Azerbaijan accused Armenia of unlawfully intervening in the formation of Artsakh, while Artsakh claimed its independence was legal under the Soviet's Law of Secession, asserting its right to self-determination. Artsakh also pointed to human rights abuses and systematic discrimination by Azerbaijan as reasons for its secession. This paper examines the legitimacy of Artsakh's secession and considers the role of alleged human rights violations by Azerbaijan for its legitimacy. International law demonstrated that practices of secession were somewhat accepted provided that a lawful ground has been adequately fulfilled as a mandatory part of divorcing a territory from its mainland. However, Artsakh’s secession from Azerbaijan is not provided by a solid, reasonable measure as a “remedial” for all the casualties that had taken place. Also, on historic ground, Artsakh failed to provide sufficient records and proof to attest to its legitimacy as a separate entity utterly detached from Azerbaijan.